POCLib: A High-Performance Framework for Enabling Near Orthogonal Processing on Compression - Zhang, Feng; Zhai, Jidong; Shen, Xipeng; Mutlu, Onur; Du, Xiaoyong (IEEE transactions on parallel and distributed systems, 2022)
Parallel technology boosts data processing in recent years, and parallel direct data processing on hierarchically compressed documents exhibits great promise. The high-performance direct data processing technique brings large savings in both time and space by removing the need for decompressing data. However, its benefits have been limited to data traversal operations; for random accesses, direct data processing is several times slower than the state-of-the-art baselines. This article proposes a novel concept, orthogonal processing on compression (orthogonal POC), which means that text analytics can be efficiently supported directly on compressed data, regardless of the type of the data processing - that is, the type of data processing is orthogonal to its capability of conducting POC. Previous proposals, such as TADOC, are not orthogonal POC. This article presents a set of techniques that successfully eliminate the limitation, and for the first time, establishes the near orthogonal POC feasibility of effectively handling both data traversal operations and random data accesses on hierarchically-compressed data. The work focuses on text data and yields a unified high-performance library, called POCLib. In a ten-node distributed Spark cluster on Amazon EC2, POCLib achieves 3.1× speedup over the state-of-the-art on random data accesses to compressed data, while preserving the capability of supporting traversal operations efficiently and providing large (3.9×) space savings.